Information sheet on future climate and impacts in the rural case studies: Tel Hadya, Syria - Sommer, Rolf (CIRCE (Climate Change and Impact Research: the Mediterranean Environment), 2011)
ENEA climate model data for the present period were able to reproduce the observed climate of northern Syria, and only required minor correction to remove a bias between the observed and model-derived data. The ENEA model projected a slight increase in annual rainfall in the near future, rather than a decrease as projected by other models. Crop model based simulations suggest that a climate change affected future with higher temperatures, elevated CO2 and slightly higher annual rainfall would not affect wheat yield significantly in comparison to the present situation. However, there is an apparent trend towards higher inter-annual variability, i.e., more years with exceptionally high or low yields. Inter-annual variability could be reduced by the application of supplemental irrigation (SI) as a potential adaptation strategy. SI water amounts were comparably modest, but could result in a 2.6 fold increase in yields. Given the uncertainty of regional climate change projections, this assessment should be expanded to include projections from other CIRCE models, before final conclusions on the impact of climate change on wheat in northern Syria can be drawn.